Contribution of superoxide dismutase and catalase activities to Shigella flexneri pathogenesis. - Franzon, V L (1990)
A Shigella flexneri serotype 5 strain deficient in the production of the iron-containing superoxide dismutase FeSOD (sodB) and a catalase-negative (katFG) S. flexneri serotype 5 strain were isolated. Both strains were examined for increased sensitivity to oxygen stress by using assays involving killing by mouse peritoneal macrophages and human polymorphonuclear leukocytes as well as infection of rabbit ileal loops. The sodB mutant was extremely sensitive to killing by phagocytes when compared with the wild-type parent, M90T. The catalase mutant also showed an increased sensitivity to killing, but to a much lesser extent. Upon infection of rabbit ileal loops and subsequent histopathological examination, the sodB mutant caused very little detectable damage to intestinal villi. The pattern of infection was roughly similar to that of BS176, an avirulent plasmidless derivative of M90T. The katFG mutant, on the other hand, showed a high degree of destruction, similar to that caused by M90T. This evidence suggests that the superoxide dismutase encoded by sodB may play an important role in the pathogenesis of S. flexneri. In contrast, catalases appear to make a limited contribution to virulence.